Cost-benefit analysis of tidal energy production in a coastal lagoon: The case of Ria Formosa – Portugal. (15th August 2021) - Rodrigues, N.; Pintassilgo, P.; Calhau, F.; González-Gorbeña, E.; Pacheco, A.
Abstract: The energy that can be extracted from tidal currents is one of the most promising renewable energy sources due to its high density/predictability. Within this paper this energy source is evaluated economically respecting sustainability principles. This evaluation contrasts from previous studies due to the application of a cost-benefit analysis based on a hydro-morphodynamic model, and moving away from the classic proxy of wind energy. It further includes, via the Monte Carlo method, a probabilistic underpinning to the project. The hydro-economic model was applied to a tidal energy project using an Evopod 1:4th scale prototype, based on a real deployment of an Evopod 1:10th scale device in the Ria Formosa, Algarve. The results show that, under the current costs and benefits, the project is not economically viable. However, there are admissible parameter ranges that make the project viable such as significant reduction of investment costs, increased capacity factors and favourable energy prices. This novel methodology has potential to be applied to other tidal energy projects on estuarine systems worldwide, and consists of a comprehensive modelling approach, including the technical, environmental, and socio-economic dimensions of the project, not only in a deterministic setting but also in a probabilistic one. Highlights: Tidal kinetic energy is evaluated economically respecting sustainability principles. Cost-benefit analysis is based on a hydro-morphodynamic model. Novel methodology with potential to be applied to other tidal energy projects. Uses data from a real deployment of a floatable tidal turbine at an inlet channel. Identified admissible parameter ranges that make the project economically viable.